Temperature effects on material behavior of aerospace aluminum alloys for subsonic and supersonic aircraft - Huda, Z.; Zaharinie, T.; Min, G.J. (American Society of Civil Engineers, 2010)
This review-cum-research paper reports the effects of temperature and time exposure on the material behavior of the aerospace aluminum alloys currently in use in subsonic and supersonic aircraft. The research reported in this paper involves experimental study of the microstructural characterization and temperature effects on the hardness behavior of the age-hardenable 2024-T3 aluminum alloy; the latter was acquired by one of the authors from Royal Malaysian Air Force (RMAF) aerospace industry. The ALCLAD 2024-T3 alloy is being used in C-130 Hercules aircraft by the RMAF. Recent research on various aluminum alloys being used and being considered for application in Concorde is also reviewed.